Structure, Biological Properties and Applications of Marine-derived Polysaccharides - Nazia Auckloo, Bibi; Wu, Bin (Current Organic Chemistry, 2016)
The marine environment is considered as a precious source of novel marinederived natural products which offer valuable, safer and affordable promising compounds. Various universities and pharmaceutical industries are more and more interested in these novel compounds due to their exceptional health benefits. Unique ingredients found in the marine biosphere are polysaccharides, polyphenols, polyunsaturated fatty acids (PUFA), enzymes and bioactive peptides, minerals and vitamins to name a few. In order, to exploit sustainably the treasures of the ocean, in depth understanding and research are a must to pave the way for a better future. This review focuses mainly on the structure, biological properties and applications of some polysaccharides derived from marine macroalgae, marine fauna as well as exopolysaccharides (EPS) from marine microorganisms.
Keywords: marine fauna